Sirtuin 1 Activator SRT1720 Protects Against Lung Injury via Reduction of Type II Alveolar Epithelial Cells Apoptosis in Emphysema. (4th July 2015) - Gu, Chao; Li, Yaqing; Xu, Wu-Lin; Yan, Jian-Ping; Xia, Ying-jie; Ma, Ying-Yu; Chen, Chun; Wang, Hui-Ju; Tao, Hou-quan
Abstract In chronic obstructive pulmonary disease (COPD), two major pathological changes that occur are the loss of alveolar structure and airspace enlargement. Type II alveolar epithelial cells (AECII) play a vital role in maintaining alveolar homeostasis and lung tissue repair. Sirtuin 1 (SIRT1), a NAD+-dependent histone deacetylase, regulates many pathophysiological processes including inflammation, apoptosis, cellular senescence and stress resistance. The main aim of this study was to investigate whether SRT1720, a pharmacological SIRT1 activator, could protect against AECII apoptosis in rats with emphysema caused by cigarette smoke exposure and intratracheal lipopolysaccharide instillation in vivo. During the induction of emphysema in rats, administration of SRT1720 improved lung function including airway resistance and pulmonary dynamic compliance. SRT1720 treatment up-regulated the levels of surfactant protein (SP)A, SPC, SIRT1 and forkhead box O 3, increased SIRT1 activity, down-regulated the level of p53 and inhibited AECII apoptosis. Lung injury caused by emphysema was alleviated after SRT1720 treatment. SRT1720 could protect against AECII apoptosis in rats with emphysema and thus could be used in COPD treatment.